Recombinant K28 antigen in ELISA in the diagnosis of canine visceral leishmaniosis - Venturin, G. L. [UNESP]; Bragato, J. P. [UNESP]; Silva, K. L.O. [UNESP]; de Lima, V. M.F. [UNESP] (Wiley, 2015)
Crude total antigen (CTA) from Leishmania infantum and recombinant antigen K39 (rK39) and recombinant antigen K28 (rK28) were compared using an ELISA for the diagnosis of canine visceral leishmaniosis (CVL). Forty-two blood samples from healthy dogs from a nonendemic area and 80 blood samples from an endemic area for dogs with visceral leishmaniosis (VL), confirmed with positive parasitological tests for Leishmania spp., were used in an ELISA. The parasitological diagnosis was chosen as a gold standard. The ELISA with rK28 antigen showed sensitivity of 100% and specificity of 100%, high agreement with CTA and rK39, indicating that the rK28 antigen is useful for ELISA serological diagnosis of CVL.
Keywords: ELISA; Leishmania infantum; Parasitic; Serology; Zoonoses